FROM HOMETOWN TO THE OVERSEAS: Tuanku Hasan Basri (THB) and His Role in Developing Tariqa Shattariyya (TS) in Medan City, Indonesia - Bakar, Abu; Hidayat, Ziaulhaq (Journal of Contemporary Islam and Muslim Societies, 2023)
Abstract: This study aimed to discuss the role of Tuanku Hasan Basri (THB) in developing Tariqa Shattariyya (TS) in Medan City. THB, a murshid of Tariqa Shattariya from Ulakan, Pariaman, West Sumatra, comes from the Pariaman community as the practitioners of TS integrated into the prevailing social traditions in Medan City. Therefore, the study question was about the role of THB in maintaining and developing TS. The method used refers to qualitative research and will present in-depth descriptive-analytical information. The approach chosen is life history, which seeks to explore and explain the history and role of the figures studied. The data source comes from the figure studied, namely THB. Data was collected using the stages of observation, interviews, and documentation. Meanwhile, data analysis is carried out by separating primary data from supporting data. Then, interpret the data. The results showed that THB played a role in increasing the number of suraus developments affiliated with TS in Medan City and lead to 27 active teaching groups as a spiritual and traditional leader.Keywords: Tariqa Shattariyya, Tuanku Hasan Basri, Surau, Local Wisdom